A multi-level examination of authentic leadership and organizational justice in uncertain times - Kiersch, Christa E., author; Byrne, Zinta, advisor; Ganster, Daniel, committee member; Gibbons, Alyssa, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2012)
Answering long-standing calls for research on how leaders influence followers and organization performance, as well as for the integration of leadership and justice research, this study proposes and tests a multi-level model of leadership, justice, and uncertainty. Building upon uncertainty management theory and the nascent research in authentic leadership, I propose a multi-level moderated mediation model wherein authentic leaders influence individual fairness perceptions and create a fair climate, which in turn is related to the well-being, turnover intention, commitment, and performance of subordinates. Uncertainty serves as a moderator in the model, such that leadership and fair climate are proposed to have a stronger relationship with employee outcomes when the level of perceived job and organizational uncertainty is high than when uncertainty is low. Survey data from 211 employees, clustered under 37 leaders (direct supervisors) is tested using a modification of Preacher et al.'s (2007, 2010) multi-level structural equation modeling (MSEM) approach. Results indicate that authentic leaders impact follower and organizational outcomes in part via directly influencing follower justice perceptions and justice climate, and that the effects of authentic leadership and justice are relatively independent of uncertainty level. This study contributes to the scientific literature by integrating theories of leadership, fairness, and uncertainty management, and by illustrating a novel and sophisticated approach (MSEM) to test this integrated model at the individual and leader levels of the organization. Implications for practice include support for authentic leadership development as an actionable strategy to bolster fairness perceptions and build a fair climate, as well as positively impact well-being, attitudinal, and behavioral intent outcomes of followers.
Keywords: organizational justice; leadership; uncertainty climate; fairness; job insecurity